Identifying Areas of Heightened Sensory Issues: Understanding Sensory Processing Disorders - Mushtaq, Tehseen; Fazil, Hina; Parveen, Zahida (Annals of Human and Social Sciences, 2024)
Sensory processing disorder (SPD), is a condition in which an individual cannot understand the sensory stimuli to the extent that it adversely affects their daily living and functioning. This study aimed to understand sensory processing disorder (SPD) and the identification of children with sensory issues while identifying areas of heightened sensory issues. A quantitative approach was employed utilizing a novel tool, Screening of Sensory Processing Disorder (SSPD) a 5-point Likert scale that assessed sensory issues across seven sensory areas. Data was collected from Therapists of children with Autism Spectrum Disorder through a cluster sampling technique. The sample size (n=140) was decided to get diverse, presentable, and real data. The results of the study were categorized into three groups: At Risk, Probable Different, and Definite Different based on scores ranging from minimum to maximum. The results of the study showed variability in scores among different categories. However vestibular and proprioceptive were reported highest in incidence based on mean score, whereas visual sensory issues were reported highest at 21% definite Different which is the highest among all categories. The study's findings showed varying levels of sensory difficulties in certain categories. The high incidence of sensory issues demands targeted intervention for addressing these unique sensory needs to cater to the relevant problems and increase the quality of life.